2013
DOI: 10.1016/j.gene.2013.07.103
|View full text |Cite
|
Sign up to set email alerts
|

Splicing variants of the porcine betaine–homocysteine S-methyltransferase gene: Implications for mammalian metabolism

Abstract: Betaine-homocysteine S-methyltransferase (BHMT) activity is only detected in the liver of rodents, but in both the liver and kidney cortex of humans and pigs; therefore, the pig was chosen as a model to define the spatial and temporal expression of BHMT during development. During fetal development, a total of ten splice variants of bhmt were expressed at varying levels across a wide range of porcine tissues. Two variants contained an identical ORF that encoded a C-terminal truncated form of BHMT (tBHMT). The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…BHMT expression and activity in foetal livers has been reported to increase with gestational age in human [5,46] and pig studies [47] which is in line with increased BHMT activity in late pregnancy that we suggest here. Interestingly, foetal liver MTR activity decreases in the third trimester [5].…”
Section: Discussionsupporting
confidence: 90%
“…BHMT expression and activity in foetal livers has been reported to increase with gestational age in human [5,46] and pig studies [47] which is in line with increased BHMT activity in late pregnancy that we suggest here. Interestingly, foetal liver MTR activity decreases in the third trimester [5].…”
Section: Discussionsupporting
confidence: 90%
“…In the process of betaine producing methionine, homocysteine is also a substrate for the enzyme action of BHMT. When the activity of BHMT decreases, the concentration of homocysteine in the blood rises, which has a certain relationship with vascular disease, thrombosis, and renal dysfunction 42,43 , these suggested that dietary 300 mg•kg −1 copper inhibited the methyl supply capacity of betaine and further affected protein biosynthesis of suckling piglets. These suggested that 300 mg•kg −1 copper did not support the methyl supply capacity of protein biosynthesis, which further devoid of integral health benefits for suckling piglets.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of betaine producing methionine, homocysteine is also a substrate for the enzyme action of BHMT. When the activity of BHMT decreases, the level of homocysteine in the blood rises, which has a certain relationship with vascular disease, thrombosis, and renal dysfunction [38,39], these suggested that 300 mg•kg -1 Cu inhibited the methyl supply capacity of betaine and further affected protein biosynthesis and the health of nursing piglets. Our previous study found that the level of pantothenic acid was decreased in the HC group [10].…”
Section: Discussionmentioning
confidence: 99%